Enhanced dissolution and systemic availability of albendazole formulated as solid dispersions - Castro, Silvina Gabriela (2013)
Solid dispersions (SDs) containing the anthelmintic compound albendazole (ABZ) and either Pluronic 188 (P 188) or polyethylene glycol 6000 (PEG 6000) as hydrophilic carriers were formulated. Drug–polymers interactions in solid state were investigated using different techniques. Only a 4% of total ABZ was dissolved at 5 min post-incubation, reaching dissolution rates of 32.8% (PEG 6000) and 69.4% (P 188) in SDs. In this way, P 188 was substantially more efficient as ABZ dissolution promoter in comparison to PEG 6000, especially at the initial stages of the dissolution processes (<30 min). An increased systemic availability (p < 0.001) was obtained when ABZ was administered as ABZ-P 188 SDs, with a 50% enhancement in systemic exposure (AUC values) compared to treatment with an ABZ suspension. Consistently, the Cmax increased 130% (p < 0.001) following treatment with P 188 based SD ABZ formulation. For the ABZ-PEG 6000 SD formulation, the favorable effect on ABZ systemic availability did not reached statistical significance compared to the control group. The study reported here showed the utility of pharmacokinetic assays performed on mice as a model for preliminary drug formulation screening studies.